Association of SEEK1 and psoriatic arthritis in two distinct Canadian populations. Issue 9 (11th February 2005) - Rahman, P; Butt, C; Siannis, F; Farewell, V T; Peddle, L; Pellett, F J; Schentag, C; Gladman, D D
Abstract : Objective: To examine the relationship between SNP +39604 in SEEK1 and psoriatic arthritis (PsA) in two distinct Canadian populations. Methods: 103 patients with PsA and 105 ethnically matched controls from Newfoundland and 202 patients with PsA and 100 controls from Ontario were studied. Patients and controls were genotyped for SNP +39604 of SEEK1 by time of flight mass spectrometry, using the Sequenom platform. Genomic DNA was amplified by the Dynal RELI SSO HLA- Cw* typing kit for HLA-C typing. Results: The frequency of the minor SEEK1 (T) allele in subjects with PsA and controls was 48.5% and 32.4%, respectively (odds ratio (OR) = 2.0; p = 0.017), in the Newfoundland population and 46.5% and 38.0%, respectively (OR = 1.4; p = 0.16), in the Ontario population. Although SEEK1 is associated with PsA, particularly in the Newfoundland population, multivariate analysis showed that SEEK1 does not seem to be a further susceptibility factor if the HLA-Cw*0602 status is already known. No association was noted between SEEK1 (T) allele and onset of psoriasis, PsA, or arthritis pattern. Conclusion: SEEK1 is associated with PsA in the Newfoundland founder population. This association is probably due to linkage disequlibrium between SEEK1 and HLA-Cw*0602 in this population.